Random And Fuzzy Measure Of Unpredictable Construction Works - Konior J. (Archives of Civil Engineering, 2015)
Supplementing well recognised practical models of project and construction management, based on probabilistic and fuzzy events may make possible to transfer the weight of the change and extra orders assessment from the qualitative form to a quantitative one. This assessment, however, is naturally burdened with an immeasurable, subjective aspect. Elaboration of probability of occurrence in a construction project unforeseen building works requires application (in addition to the non-measureable, qualitative criteria) of measurable (quantitative) criteria which still appear during construction project implementation. In reimbursable engineering contracts, a random event described as an extra, supplementary building work has a random character and occurs with a specific likelihood. In lump sum contracts, on the other hand, such a random event has a fuzzy character and its occurrence is defined in a linear manner by the function of affiliation to the set of fuzzy events being identical with unforeseen events. The strive for quantitative presentation of criteria regarded by nature as qualitative and the intention to determine relations between them led to the application of the fuzzy sets theory to this issue. Their properties enable description of the unforeseen works of construction projects in an unambiguous, quantitative way.